The FUSION protein crystallization screen. Issue 2 (11th March 2022) - Gorrec, Fabrice; Bellini, Dom
Abstract : The FUSION protein crystallization screen, which integrates 96 unique combinations of additives, is presented and its efficiency is demonstrated. Abstract : The success and speed of atomic structure determination of biological macromolecules by X‐ray crystallography depends critically on the availability of diffraction‐quality crystals. However, the process of screening crystallization conditions often consumes large amounts of sample and time. An innovative protein crystallization screen formulation called FUSION has been developed to help with the production of useful crystals. The concept behind the formulation of FUSION was to combine the most efficient components from the three MORPHEUS screens into a single screen using a systematic approach. The resulting formulation integrates 96 unique combinations of crystallization additives. Most of these additives are small molecules and ions frequently found in crystal structures of the Protein Data Bank (PDB), where they bind proteins and complexes. The efficiency of FUSION is demonstrated by obtaining high yields of diffraction‐quality crystals for seven different test proteins. In the process, two crystal forms not currently in the PDB for the proteins α‐amylase and avidin were discovered.